1998
DOI: 10.1098/rspb.1998.0503
|View full text |Cite
|
Sign up to set email alerts
|

Baculovirus resistance in the noctuid Spodoptera exempta is phenotypically plastic and responds to population density

Abstract: Parasite resistance mechanisms can be costly to maintain. We would therefore predict that organisms should invest in resistance only when it is likely to be required. Insects that show density-dependent phase polyphenism, developing di¡erent phenotypes at high and low population densities, have the opportunity to match their levels of investment in resistance with the likelihood of exposure to pathogens. As high population densities often precipitate disease epidemics, the high-density form should be selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
198
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(207 citation statements)
references
References 35 publications
7
198
1
1
Order By: Relevance
“…Hence, this paper is the ¢rst demonstration, to our knowledge, that DDP occurs against a non-speci¢c pathogen in a host from a population not previously exposed to it. The similarity of the results presented here with those of Reeson et al (1998) (i.e. insects reared at high density were found to be more pathogen resistant) and the fact that the system used is non-speci¢c suggests that plasticity in immune investment is a common response to £uctuations in population density, at least in insects exhibiting other density-dependent polyphenisms.…”
Section: Discussionsupporting
confidence: 74%
“…Hence, this paper is the ¢rst demonstration, to our knowledge, that DDP occurs against a non-speci¢c pathogen in a host from a population not previously exposed to it. The similarity of the results presented here with those of Reeson et al (1998) (i.e. insects reared at high density were found to be more pathogen resistant) and the fact that the system used is non-speci¢c suggests that plasticity in immune investment is a common response to £uctuations in population density, at least in insects exhibiting other density-dependent polyphenisms.…”
Section: Discussionsupporting
confidence: 74%
“…For example, Reeson et al (1998) showed that larvae of the African armyworm, Spodoptera exempta, that had been reared at high densities had significantly higher haemolymph PO levels and higher NPV resistance than those reared solitarily (Reeson et al, 1998). However, as far as we are aware, a direct link between PO activity and intra-specific variation in parasite resistance has yet to be conclusively demonstrated.…”
Section: Introductionmentioning
confidence: 96%
“…Heredity (2002) 88, 229-234. DOI: 10.1038/sj/hdy/6800031 1998; Reeson et al, 1998). However, PO in other parts of the body may also play an important role in immunity.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively few parasites are known from social insects, in spite of their abundance and ecological dominance (Schmid-Hempel, 1998). This may relate to a genuine paucity, possibly resulting from a reduction in intergroup interactions (Wilson et al, 2003), or from the effective defences group-living insects can show, such as density-dependent immune defence (Barnes and SivaJothy, 2000;Reeson et al, 1998;Wilson et al, 2002), and enhanced behavioural or antimicrobial defences of groups against diseases Rosengaus et al, 1998;Traniello et al, 2002). There are, however, very few published surveys of the natural prevalence of social insect parasites.…”
Section: Introductionmentioning
confidence: 99%